Predicting independent walking ability using the Simplified Stroke Rehabilitation Assessment of Movement, Berg Balance Scale, and Barthel Index for Activities of Daily Living in individuals post-stroke: an observational preliminary study - Mykola Romanyshyn (Physiotherapy Quarterly)
Introduction The purpose of this study was to determine cut scores to predict independent ambulation for the Simplified Stroke Rehabilitation Assessment of Movement (S-STREAM), Berg Balance Scale (BBS), Barthel Index (BI) for Activities of Daily Living for patients with time after stroke up to 1 year. The study’s second goal was to establish statistical dependence between the tests the S-STREAM, BBS, BI, and the Functional Ambulation Category (FAC).